2018
DOI: 10.3389/fpsyt.2018.00315
|View full text |Cite
|
Sign up to set email alerts
|

Increased Attentional Bias Toward Visual Cues in Internet Gaming Disorder and Obsessive-Compulsive Disorder: An Event-Related Potential Study

Abstract: Internet gaming disorder (IGD) is a newly identified potential addiction disorder associated with compulsive internet-game playing behavior and attentional bias toward online gaming- related cues. Attentional bias toward addiction-related cues is the core feature of addiction that is associated with craving, but the pathophysiology of attentional bias in IGD is not well-understood, such as its relationship to compulsivity. In this study, we used the electrophysiological marker of late positive potential (LPP) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 44 publications
(68 reference statements)
2
29
0
Order By: Relevance
“…In this study, decreased activations were found in the lentiform nucleus and other reward-related brain regions after recovery. The findings suggest that neural response to gaming cues decreases following recovery, which is consistent with previous studies comparing IGD with controls (Kim et al, 2018;Ko et al, 2013;Ma et al, 2019). The correlations between decreases in lentiform activation and self-reported cue-elicited craving provide support to the notion that decreased neural reactivity in the lentiform may underlie decreased cue-elicited craving responses in recovery in IGD and may relate importantly to diminished motivations to engage excessively in gaming behaviors.…”
Section: Decreased Sensitivity To Gaming Cuessupporting
confidence: 89%
See 2 more Smart Citations
“…In this study, decreased activations were found in the lentiform nucleus and other reward-related brain regions after recovery. The findings suggest that neural response to gaming cues decreases following recovery, which is consistent with previous studies comparing IGD with controls (Kim et al, 2018;Ko et al, 2013;Ma et al, 2019). The correlations between decreases in lentiform activation and self-reported cue-elicited craving provide support to the notion that decreased neural reactivity in the lentiform may underlie decreased cue-elicited craving responses in recovery in IGD and may relate importantly to diminished motivations to engage excessively in gaming behaviors.…”
Section: Decreased Sensitivity To Gaming Cuessupporting
confidence: 89%
“…Like drug cues in drug addictions, gaming cues may trigger game-seeking behaviors in IGD (Dong & Potenza, 2016). IGD participants have exhibited higher cue-induced brain features in the ventral and dorsal striatum (Liu et al, 2017), altered functional networks (Ko et al, 2013;Ma et al, 2019), higher late positive potential amplitude (Kim et al, 2018), when compared with control subjects when exposed to gaming cues. Neural responses to gaming cues may predict the emergence of IGD (Dong, Wang, Liu, et al, 2019) and operate in a gender-sensitive fashion .…”
Section: Cue Reactivity and Craving In Igdmentioning
confidence: 99%
See 1 more Smart Citation
“…Binge Watching, Gaming, Gambling ( He et al, 2019 ) P100 90–150 PO5, PO6 Internet Gaming Disorder [playing the online game “Strike of Kings”] (15) vs. HC (15) IAT score > 79, IGAS score > 7, DSM-5 criteria of IGD as assessed by clinical interview Cartoon faces out “Strike of Kings” vs. Realistic faces IGD: Larger amplitude for cartoon vs. realistic faces in left hemisphere HC: No difference N170 150–210 IGD: Larger amplitude for cartoon faces vs. realistic faces in right hemisphere HC: Larger amplitude for cartoon faces vs. realistic faces in both hemispheres P200 210–270 IGD: Larger amplitude for cartoon faces vs. realistic faces in both hemispheres HC: No difference ( Kim et al, 2018 ) LPP 350–700 CP1, CPz, CP2, P1, Pz , P2 Internet Gaming Disorder (20) vs. HC (23) vs. Obsessive-Compulsive Disorder (20) Playing one of three games (League of Legend, FIFA, Sudden Attack) for > 4 h/day Game related (League of Legend, FIFA, Sudden Attack) vs. OCD related vs. neutral images IGD > HC for LPP to game-related cues (but not for OCD related cues). Limitation: effect was not found for all electrode sites, not controlled for multiple testing ( Lai et al, 2017 ) LPP 200–300, 300–400, 400–500.…”
Section: Introductionmentioning
confidence: 99%
“…Both OCD and IGD are most prevalent during early adolescence, which is a critical period for learning and social development (Kessler et al, 2007 ). In addition, both OCD and IGD has repetitive thought and attentional bias to a specific object or target related with their symptom (Tata et al, 1996 ; Bradley et al, 2016 ; Kim et al, 2018 ). Because those symptoms affect attentional capacity which is a very basic unit of cognitive functioning, broad range of cognitive functioning can be affected by symptoms of OCD and IGD.…”
Section: Introductionmentioning
confidence: 99%